Monitoring the t → m Martensitic Phase Transformation by Photoluminescence Emission in Eu3+‐Doped Zirconia Powders. Issue 8 (26th April 2013) - Marin, Riccardo; Sponchia, Gabriele; Zucchetta, Enrico; Riello, Pietro; Enrichi, Francesco; De, Goffredo; Benedetti, Alvise; Rohrer, G.
<x xml:space="preserve">Abstract</x> In this work, we demonstrate that the martensitic t → m phase transformation of ZrO2 powder stabilized with Eu3+ and Eu3+/Y3+ ions, can be effectively monitored by photoluminescence (PL) spectroscopy. As the luminescent properties of Eu3+ from within a host lattice are strongly influenced by the coordination geometry of the ion, we used the emission spectrum to monitor structural changes of ZrO2. We synthesized Eu3+‐doped and Eu3+/Y3+‐codoped samples via the coprecipitation method, followed by calcination. We promoted the martensitic transformation by applying mechanical compression cycles with an increasing pressure, and deduced the consequential structural changes from the relative intensities of the 5D0→7F2 hypersensitive transitions, centered, respectively, at 606 and 613 nm whether the Eu3+ is in the eightfold coordinated site of the tetragonal phase or in the sevenfold coordinated site of the monoclinic phase. We suggest that the unique emission profile for Eu3+ ions in different symmetry sites can be exploited as a simple analytical tool for remote testing of mechanical components that are already mounted and in use. The structural changes observed by PL spectroscopy were corroborated by X‐ray powder diffraction (XRPD), with the phase compositions and volume fractions being determined by Rietveld analysis.